2010
DOI: 10.5251/abjna.2010.1.3.307.312
|View full text |Cite
|
Sign up to set email alerts
|

Activity of ethanolic extract of Clerodendrum violaceum leaves against Plasmodium berghei in mice

Abstract: The antimalarial potential of the ethanolic extract of Clerodendrum violaceum leaves (13 mg/kg body weight) was investigated in mice infected with Plasmodium berghei. Haematological indices including the red blood cell indices, the white blood cell indices and platelet count were also evaluated on days 3, 8 and 14 after infection. Phytochemical screening revealed a predominance of alkaloids (3.68 %), and phenolics (2.78 %) in the extract. The extract suppressed parasitaemia following administration to infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
3
21
1
Order By: Relevance
“…(11) Many research studies of medicinal plants have shown them to have antimalarial activity by inducing the synthesis of red blood cells, white blood cells and platelets. (20,21) A limitation of this study is that the leukocyte profile data were obtained by using blood smear preparations only, whereas specialized tools are required such as heme analyzers to obtain results with better validity. The clinical implication of this study is that this exposure model of artemisinin with in vivo repeated passages in mice infected with P.berghei can be used as a basis to describe the functioning of the immune system against infections with P. berghei parasites which have been exposed to repeated artemisinin.…”
Section: Discussionmentioning
confidence: 99%
“…(11) Many research studies of medicinal plants have shown them to have antimalarial activity by inducing the synthesis of red blood cells, white blood cells and platelets. (20,21) A limitation of this study is that the leukocyte profile data were obtained by using blood smear preparations only, whereas specialized tools are required such as heme analyzers to obtain results with better validity. The clinical implication of this study is that this exposure model of artemisinin with in vivo repeated passages in mice infected with P.berghei can be used as a basis to describe the functioning of the immune system against infections with P. berghei parasites which have been exposed to repeated artemisinin.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the symptoms of malaria in human include headache, muscle pain, stress, nausea, vomiting, fatigue, weakness and in extreme cases of cerebral malaria [23] . There are many reports due to effects of some chemical and natural compound with different doses against P. berghei [24,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Methods: In this study, 48 adult male mice, (20)(21)(22)(23)(24)(25) 8 when compared to that on day 0, whereas it was 9% on day 9. There was no orchitis found in this group.…”
Section: Plasmodium Bergheimentioning
confidence: 99%
See 1 more Smart Citation
“…Clerodendrum violaceum Gürke (Verbenaceae) is commonly called Clerodendrum in English and "Ewe isedun" in Yoruba (Nigeria); a decoction of the leaves is used for the treatment of fever/malaria. Our previous studies have authenticated the acclaimed antimalarial activity of its leaf extract in folk medicine (Balogun et al, 2010). However, there is paucity of information on the possible amelioration of secondary ROS-mediated pathological conditions associated with malaria.…”
Section: Introductionmentioning
confidence: 99%